DETERMINANTS OF WORK ENGAGEMENT DURING PANDEMIC: THE CASE OF ISLAMIC BANKING WORKERS - Syayyidah Maftuhatul Jannah; Rasistia Wisandianing Primadineska (Bank Indonesia, 2022)
This study analyzes the role of emotional intelligence and resilience in work engagement of employees in the Islamic banking industry during the Covid-19 pandemic. To this end, it gathers data from 364 Islamic bank employees. Using the PLS-SEM for data analysis, the results show positive and significant effects of emotional intelligence and resilience on the work engagement. The emotional intelligence also had a positive influence on resilience. This shows that positive forces from within the individual affect the productivity of organizational members during current pandemic. The implication of the results of this study for management is the need for special attention toward developing the positive potential of individuals so that each member of the organization has good emotional intelligence and resilience.